Improvement in cognitive biases after group psychoeducation and metacognitive training in recent-onset psychosis: A randomized crossover clinical trial. (December 2018) - Ahuir, Maribel; Cabezas, Ángel; Miñano, Maria José; Algora, Maria José; Estrada, Francesc; Solé, Montse; Gutiérrez-Zotes, Alfonso; Tost, Meritxell; Barbero, Juan David; Montalvo, Itziar; Sánchez-Gistau, Vanessa; Monreal, José Antonio; et al.
Highlights: We studied changes in cognitive biases after group therapy in recent-onset psychosis. A randomized crossover pilot clinical trial was conducted in stable patients. Metacognitive therapy (MCT) and psychoeducation (PE) were administered. Two sequences were compared: MCT + PE vs PE + MCT. Cognitive biases and depressive symptoms improved similarly in both groups. Abstract: Metacognitive training (MCT) improves cognitive biases in psychosis. We aimed to explore whether the effectiveness of the combination of psychoeducation and MCT group treatments on cognitive biases differed if the combination was started by psychoeducation or by MCT. Fourty-nine stable patients with a recent-onset psychosis were randomized to two different sequences: MCT + psychoeducation vs psychoeducation + MCT. Cognitive biases, psychopathology symptoms, insight and functioning were assessed. Cognitive biases and depressive symptoms improved with both group interventions, without differential effects between both sequences. Our study suggests that MCT and psychoeducation are useful in improving cognitive biases and depressive symptoms in recent-onset psychosis.